Meningkatkan Kemampuan Bertanya Anak Usia Dini melalui Eksperimen Sains di Kober Nurul Huda - Engkar, Silma Rahbani (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2024)
The author's interest in using science experiments at Kober Nurul Huda to enhance young children's ability to ask questions drove this research. It highlights the significance of early childhood education (PGPAUD) as guidance for children from birth to six years of age, citing Law 20 of 2003 concerning the National Education System. According to Montesori and other theories of education, children develop very quickly at this age in a number of areas. Nonetheless, Kober Nurul Huda observations revealed that the majority of kids were less engaged in asking questions, leading to the conclusion that kids' skills needed to be developed. Thus, the purpose of this study is to assess how science experiments at Kober Nurul Huda affect young children's ability to ask questions and to enhance that ability in young children. 17 children participated in three research cycles using a classroom action research (PTK) approach, and data was gathered through observation, documentation sheets, and both quantitative and qualitative data analysis. The study's findings demonstrate that young children at Kober Nurul Huda have significantly improved their ability to ask questions, as evidenced by cycles II and III. This improvement is particularly evident in their capacity to ask questions without feeling uncomfortable. Therefore, it can be said that science experiments help young children in Kober Nurul Huda develop their ability to ask questions.